A Semmelweis Orvostörténeti Könyvtár gyűjteményének története - Kapronczay, Katalin; Magyar, László András (Per Aspera ad Astra, 2016)
Present article gives a short overview on the history of the collection of the Semmelweis Library for the History of Medicine, Budapest. This collection was established in 1837 as the library of the recently founded Budapest Royal Society of Physicians. Its aim was the promotion of the education and training of local doctors and students of medicine. The library was successfully managed and enlarged up to the WW I. In the period between the two wars however the Society had to face serious difficulties, due partly to the influence of politics, partly to constant financial problems. The library luckily survived the wartime bombings. In 1947 the Budapest Royal Society of Physicians was banned by the communist regime. Its library has been transformed into the so called National Library for History of Medicine, (later Semmelweis Library for the History of Medicine) founded in 1951 by the Ministry of Health. Since 1951 the library hasn’t functioned anymore as a medical, but „only” as a medical historical collection. The collection – containing now 140 000 volumes – still exists in the frame of the Semmelweis Museum, Library and Archives, having however rather loose connections with medical education.